2013
DOI: 10.3758/s13423-013-0416-1
|View full text |Cite
|
Sign up to set email alerts
|

25 years of research on the use of geometry in spatial reorientation: a current theoretical perspective

Abstract: The purpose of this article is to review and evaluate the range of theories proposed to explain findings on the use of geometry in reorientation. We consider five key approaches and models associated with them and, in the course of reviewing each approach, five key issues. First, we take up modularity theory itself, as recently revised by Lee and Spelke (Cognitive Psychology, 61, 152-176, 2010a; Experimental Brain Research, 206, 179-188, 2010b). In this context, we discuss issues concerning the basic distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
163
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(181 citation statements)
references
References 156 publications
(218 reference statements)
12
163
0
6
Order By: Relevance
“…By contrast, heading retrieval might involve interpreting the environment in terms of a spatial reference system from which orientational axes can be recovered (14). Although the precise computations underlying heading retrieval are unknown, previous work suggests that at least for humans, heading retrieval is not performed by view matching (4,19,20). (See SI Discussion 2 for further consideration of the implications of the present experiments for viewmatching theories of reorientation.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…By contrast, heading retrieval might involve interpreting the environment in terms of a spatial reference system from which orientational axes can be recovered (14). Although the precise computations underlying heading retrieval are unknown, previous work suggests that at least for humans, heading retrieval is not performed by view matching (4,19,20). (See SI Discussion 2 for further consideration of the implications of the present experiments for viewmatching theories of reorientation.…”
Section: Discussionmentioning
confidence: 82%
“…We use a variant of a spatial reorientation task that has been used extensively to study navigation behavior in a variety of species, including rodents and human children (4)(5)(6)(7). In the standard version of the task, the animal (or human) navigator is first familiarized with a rectangular chamber with a hidden reward in one of the corners.…”
mentioning
confidence: 99%
“…Thus the spaces occupied and explored by children become significant not only for mapping but also for understanding basic geometric concepts such as boundedness, flat-ness, parallels, perpendiculars, curves, distance, and mapping. Young children use both geometric features of their surroundings as well as landmarks to find their way around spaces (Cheng, Huttenlocher, & Newcombe 2013). For example, Lee, Sovrano, and Spelke (2012) found that 2 year olds used surface distances and directions.…”
Section: Studies Emerging From the Cognitive Sciencesmentioning
confidence: 99%
“…Over the last three decades, much attention has been focused on the use of geometric relationships of enclosures for locating a goal (reviewed in Cheng et al 2013). For example, when trained to locate a reward in one of the four corners inside a rectangular enclosure, an experimentally-disoriented animal typically chooses, with approximately equal probability, either the correct corner or the diagonally-opposing corner (the "geometric error") during a test.…”
Section: Introductionmentioning
confidence: 99%